Russell Maliphant Company Review - Meisner, Nadine (Dance Books Ltd., Alton,Hampshire (UK), 2001)
PALABRAS CLAVE: Russell Maliphant Company, Two, Knot, Stream, Sheer.
Dentro del apartado "Dance Now. Flying High. Dance Umbrella 2001".